AN OPEN SOURCE VIRTUAL MANIPULATIVE FOR TEACHING 3 DIMENSIONAL GEOMETRIC OBJECTS: GOOGLE SKETCHUP - Erkoc, M. Fatih; Erkoc, Cigdem (IATED-INT ASSOC TECHNOLOGY EDUCATION A& DEVELOPMENT, 2012)
Mathematic that contains many abstract concepts is a major problem for elementary school students who have difficulty embodying these concepts. Especially, geometric shapes are tried to embodying by sketched on paper with the help of ruler, protractor and compass to students. However, transferring on paper of three dimensional geometric objects that is more abstract concept, and require high level embodying and spatial visualization ability is not very effective to embodying. In traditional learning environments, models and metaphors are often used in teaching three dimensional geometric objects. But, these methods are not always able to provide the necessary effect. Advantage of the opportunities offered by information technologies, three dimensional geometric objects can be embodied in the minds of students. In this study, Google SketchUp that is an open source sketching software that can be used for teaching three dimensional geometric objects is analyzed as a virtual manipulative. Google SketchUp that has user-friendly and simple interface can used by teachers easily. Google Sketchup software, which offering a funny sketching environment for students, is thought to be effective for embodied of three dimensional objects by students.
Keywords: virtual manipulative; Google SketchUp; geometry; geometric objects; Education & Educational Research